Sacred Scripture Consists More in Grace than in Letter - Manresa Lamarca, Ignacio M (Biblica et Patristica Thoruniensia, 2025)
This article intends to demonstrate that St. Thomas affirmed that Sacred Scripture, understood in analogy with Sacra Doctrina, —that is, as the act by which God teaches us through Sacred Scripture— consists more in the infusion of the grace of the Holy Spirit than rather than the text itself. After establishing that Aquinas conceptualized it in this manner, we provide insights into the implications of principle principle for the biblical hermeneutics of St. Thomas Aquinas.